Mindfulness based interventions in the treatment of obesity - Winiarz, Aleksandra; Wokurka , Wojciech; Turek, Michał; Szlendak, Paula; Toś, Katarzyna; Wojtala, Kacper; Grosman, Sylwia; Węgrzyniak, Agata; Drobek, Dominik; Wąsala, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Obesity is a chronic, multifactorial disease that leads to many complications. Many methods of treating obesity are available, but they are often not effective enough. Due to the strong connection between psychological factors and the development of obesity, it can be useful to include mindfulness training in treatment. The aim of this study: Summarize current knowledge on the effectiveness of mindfulness training in the treatment of obesity and evaluate the effect of mindfulness on weight loss. Material and method: The review includes publications published in 2012-2022. The search of publications in the Pubmed database was carried out using the following keywords: mindful eating, mindfulness, weight loss, obesity. Description of the stage of the knowledge: The use of mindfulness techniques in the treatment of eating disorders is becoming more popular. A growing number of studies evaluating the effects of mindfulness on weight loss are emerging, but the results are inconclusive. Mindfulness training is effective in improving eating habits and promoting lifestyle changes. Mindfulness training combined with behavioral treatments for obesity has positive effects on weight loss. Summary: Research shows that mindfulness training may be a promising intervention in obesity treatment because it increases self-awareness and promotes lifestyle changes. However, more research is needed to assess the long-term effectiveness of mindfulness for weight control.